Estudo e aplicações da geometria fractal - Rabay, Yara Silvia Freire (2013)
Here we present a research about fractals, its history, mathematical concepts and applications. Some constructions were developed using some basic concepts of the Theory of Numbers, Trigonometry and Linear Algebra that can be applied in High School. We presented some activities that can be applied in High School’s classes in order to develop mathematical concepts such as geometric transformations, Geometry, Trigonometry, Logarithm, notions of limit among other topics. Keywords: Fractal Geometry, Geometric Transformation, Logarithm, Pascal Triangle, Arrays, Linear Algebra, High School.